Application of Virtual Assistant Academic Activities Of Students And Lecturers Based On Web And Mobile - Diana Diana; Yulia Darmi; Ujang Juhardi; Wigu Oktrabio Setiawan (Penerbit Jurnal Indonesia, 2022)
Academic activities are daily operational activities that occur in an educational institution, especially in universities. Academic activities must be carried out by students and lecturers. Within the scope of academic activities at the Faculty of Engineering, University of Muhammadiyah Bengkulu, the media used to convey information on the current academic schedule no longer uses bulletin boards but uses social media, namely whatsapp. Although academic activities are routine, it is still common for students and lecturers to forget the schedule of academic activities. To overcome this, the Faculty of Engineering requires a personal digital assistant application (virtual assistant) as an accurate, efficient and portable reminder. The virtual assistant application that is built consists of two platforms. First, the mobile platform used by lecturers and students to view some academic agenda information and receive real-time information/announcements and notifications/alarms related to academic activities. Second, the web platform used by the Administration to broadcast announcements or invitations to mobile application users. Based on the test results, the virtual assistant application can run on two platforms.